The Influence of Shuttle-Shape Emodin Nanoparticles on the Streptococcus suis Biofilm - Ding, Wenya; Sun, Jin; Lian, He; Xu, Changgeng; Liu, Xin; Zheng, Sidi; Zhang, Dong; Han, Xiaopeng; Liu, Yanyan; Chen, Xueying; God′spower, Bello O.; Li, Yanhua (Frontiers in Pharmacology, 2018)
Biofilm is one of the most important physiological protective barriers to the Streptococcus suis (S. suis), and it is also one of the primary causes of hindrance to drug infiltration, reduction of bactericidal effects and the development of antibiotic resistance. In order to intervene or eliminate S. suis biofilm, a shuttle-shape emodin-loaded nanoparticle was developed in our study. The emodin nanoparticle was prepared by emodin and Geltin-CD which was synthesize as drug carrier, and the nanoparticle was 174 nm in size, -4.64 mv in zeta potentials and exhibited a sustained emodin release. Moreover, the delivery mechanism of nanoparticle was also explored in our study. The confocal laser scanning microscopy and colony forming unit enumeration experiment indicated that nanoparticle could increase drug infiltration and uptake by biofilm. The flow cytometry system analysis showed that nanoparticle could be up taken by 99% of the bacteria cells. TCP assay and scanning electron microscopy showed that the nanoparticle had better effect on biofilm inhibition and elimination when compared with emodin solution. These results revealed that the emodin nanoparticle had a better therapeutic effect on the S. suis biofilm in vitro.